Surface Engineering‐Induced d‐Band Center Down‐Regulation in High‐Entropy Alloy Nanowires for Enhanced Nanozyme Catalysis - Kunyang Feng; Hanting Wang; Song Zhou; Wei Zhang; Chonghai Gong; Yuxin He; Yusen Wang; Wenchong Dai; Jianbo Li; Zhengwei Zhang; Siqiao Li (Advanced Science)
Abstract High‐entropy alloys (HEAs) have garnered extensive attention owing to their broad compositional tunability and high catalytic activity. However, precisely modulating the enzyme‐like activity of HEAs and enhancing their biocompatibility for biological applications remain severely challenging. Herein, PtRuFeCoNi HEA nanowires (NWs) are synthesized by adjusting the metal composition and surface‐engineered with polydopamine (PDA) to form HEA NWs@PDA nanozymes (HEzymes@PDA) with superior catalytic activity and photothermal properties. Density functional theory calculations and the Sabatier principle reveal that self‐polymerized PDA surface engineering moderately lowers the d‐band center of the HEAs, optimizes the surface charge distribution, and enhances the adsorption–desorption efficiency of the substrates. As a proof‐of‐concept, the HEzymes@PDA are synergistically integrated with hydrogels for biosensing analysis. This study presents an innovative paradigm for designing highly active HEA nanozymes via surface engineering and demonstrates their immense potential in catalytic sensing applications.